LITERARY ARTS PROVIDING HARMONY IN POEMS OF SEYYID NESIMI - Nazmi ÖZEROL (Fırat University, 2019)
In the wake of constitution of Classical Turkish poetry in 14th century, Seyyid Nesimi is an exceptional person in terms of creating an original style with his rich sound and sincere genre in a period in which many things weren’t in its definite place. As his poetic might stayed under the shade of ideological statements, the artist couldn’t come to the place he deserved. When his poems were are examined, it can be seen that he constitutes a poetry language which can’t easily get old even if years pass. Most of theim portant elements that make his poems become lasting are his in